Prayer and poetry in the Dead Sea Scrolls and related literature : essays on prayer and poetry in the Dead Sea scrolls and related literature in honor of Eileen Schuller on the occasion of her 65th birthday - Schuller, Eileen M., 1946-; Penner, Jeremy; Penner, Ken M.; Wassen, Cecilia, 1962- (Studies on the texts of the desert of Judah, 2012)
A timely collection of contributions by major scholars in the field of prayer and poetry in the Dead Sea Scrolls.